A Sustainable environmental change and ESG initiatives by the manufacturing and others service Industries during COVID19 Pandemic. Issue 1 (November 2021) - Mittal, Monika; Pareek, Manoj; Sharma, Shubham; Chohan, Jasgurpreet; Kumar, Raman; Singh, Sandeep
Abstract: Covid-19 has improved the economy's ESG plan. The ESG rating of an industry is crucial for stakeholders and will influence future business practices. ESG is commonly understood to refer to a set of criteria for making long-term investments in the areas of the environment, social welfare, and governance. Climate change is a systemic concern, and governments, companies, and society are increasingly determined to meet it. Climate change, according to the ESG, is the world's most complicated challenge, posing collective risk and ambiguity to society. The impact of ESG elements and climate risk in the insurance business is investigated in this research. The research will also look into how insurers are responding to climate change. The research will also look into how insurers are pursuing climate-friendly activities such as creating green jobs, supporting socially responsible investing, and prioritizing environmental, social, and governance (ESG) and commercial sustainability in their operations. As a result, the study's major recommendation is that potential clients and insurers increase their horizons of ESG risk awareness.